Spinoza and neuropsychology: a comparison of theories of emotion, methodology and ontology - Rice, Sheldon Stephen (My University, 1989)
This paper deals with the mind-body problem in Spinoza's Ethics and in neuro- or physiological psychology. The thesis is twofold: a) that the psychology offered by Spinoza has much in common with neuropsychology; b) that Spinoza's methodology is in some ways superior to the predominant neuro-scientific one. I also argue, though not conclusively, the superiority of Spinoza's ontology. The discussion is grounded in a comparison of the respective psychologies of emotion.
Keywords: ethics; neuropsychology; Spinoza